Awareness, Usage and Benefits of Electronic-Governance Information among Patrons of Public Libraries in South-West, Nigeria - Buhari, Ganiyu Idowu; Ajayi, Stephen Adekunle; Abdulsalam, JamiuAdewale; Oyewole, Saheed Oluwasegun; Awolusi, Comfort Oluwapelumi (Communicate: Journal of Library and Information Science, 2025)
The adoption of electronic governance by the citizens is expected to usher in tremendous benefits to both government and governed. Citizen engagement and political participation through effective dissemination and management of information shall be the order of the day. This study investigated levels of awareness, usage and the perceived benefits of e-government information among patrons of public libraries. The study adopted a descriptive survey research design of quantitative (Questionnaire) method to collect data. The population of the study is 10,969. The study adopted a simple random sampling technique, and using Yamane (1967) formula for calculating it, a sample size of 386 was arrived at. To give more respondents opportunities, the researchers adopted 400 as a sample size for the study. The data collected were analyzed using descriptive statistics of frequency and percentages. The finding revealed that the level of awareness of e-government portals is low (63.5%), with few patrons patronising the e-government portal for service delivery (59.8%). The finding offers a positive perception of the benefits of the e-government portal, believing that it can benefit service delivery. The study recommended, among others, that Public libraries engage in creating awareness of the benefits of using e-government portals for various government services.